Lesions causing central sleep apnea localize to one common brain network - Taoyang Yuan; Zhentao Zuo; Zhentao Zuo; Zhentao Zuo; Jianguo Xu (Frontiers Media S.A., 2022)
ObjectivesTo characterize the specific brain regions for central sleep apnea (CSA) and identify its functional connectivity network.MethodsWe performed a literature search and identified 27 brain injuries causing CSA. We used a recently validated methodology termed "lesion network mapping" to identify the functional brain network subtending the pathophysiology of CSA. Two separate statistical approaches, the two-sample t-test and the Liebermeister test, were used to evaluate the specificity of this network for CSA through a comparison of our results with those of two other neurological syndromes. An additional independent cohort of six CSA cases was used to assess reproducibility.ResultsOur results showed that, despite lesions causing CSA being heterogeneous for brain localization, they share a common brain network defined by connectivity to the middle cingulate gyrus and bilateral cerebellar posterior lobes. This CSA-associated connectivity pattern was unique when compared with lesions causing the other two neurological syndromes. The CAS-specific regions were replicated by the additional independent cohort of six CSA cases. Finally, we found that all lesions causing CSA aligned well with the network defined by connectivity to the cingulate gyrus and bilateral cerebellar posterior lobes.ConclusionOur results suggest that brain injuries responsible for CSA are part of a common brain network defined by connectivity to the middle cingulate gyrus and bilateral cerebellar posterior lobes, lending insight into the neuroanatomical substrate of CSA.